2019
DOI: 10.1038/s41467-019-11239-0
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial activity of primaquine operates via a two-step biochemical relay

Abstract: Primaquine (PQ) is an essential antimalarial drug but despite being developed over 70 years ago, its mode of action is unclear. Here, we demonstrate that hydroxylated-PQ metabolites (OH-PQm) are responsible for efficacy against liver and sexual transmission stages of Plasmodium falciparum . The antimalarial activity of PQ against liver stages depends on host CYP2D6 status, whilst OH-PQm display direct, CYP2D6-independent, activity. PQ requires hepatic metabolism to exert activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 36 publications
4
108
0
3
Order By: Relevance
“…The resulting amino-phenol undergoes facile oxidation to the quinone-imine by oxygen resulting in generation of ROS. In the presence of the flavoenzyme cytochrome P450 NADPH:oxidoreductase, the quinone-imine is reduced to the amino-phenol, and thus redox cycling ensues (Camarda et al, 2019). It is the ROS that exert cytotoxicity toward gametocytes; this redox cycling precisely mirrors the process as described above for methylene blue.…”
Section: Discussionmentioning
confidence: 86%
“…The resulting amino-phenol undergoes facile oxidation to the quinone-imine by oxygen resulting in generation of ROS. In the presence of the flavoenzyme cytochrome P450 NADPH:oxidoreductase, the quinone-imine is reduced to the amino-phenol, and thus redox cycling ensues (Camarda et al, 2019). It is the ROS that exert cytotoxicity toward gametocytes; this redox cycling precisely mirrors the process as described above for methylene blue.…”
Section: Discussionmentioning
confidence: 86%
“…Specifically, 4AQs kill malaria parasites with the same mode of action as has been proposed for their anti-coronavirus effects, by increasing intravacuolar pH [22,24]. While mechanisms of action of 8AQs are poorly defined, recent studies have suggested malaria parasites are killed site-specifically by hydrogen peroxide accumulation generated by a two-step biochemical relay involving monooxygenases and cytochrome P450:NADPH oxidoreductase [6]. Also, tafenoquine is active against the lung pathogen Pneumocystis in vitro and in vivo at pharmacologically relevant concentrations and doses [4,16].…”
Section: Manuscript Textmentioning
confidence: 97%
“…Tafenoquine [TQ], an FDA-approved 8-aminoquinoline [8AQ] antimalarial, can be administered orally, weekly, for up to six months, and is differentiated relative to the 4-aminoquinolines [4AQs] hydroxychloroquine (HCQ) and chloroquine (CQ) in that it does not prolong QTc interval and acts more broadly against a variety of malaria life cycle stages via different mechanisms of action [1, 6,10]. Specifically, 4AQs kill malaria parasites with the same mode of action as has been proposed for their anti-coronavirus effects, by increasing intravacuolar pH [22,24].…”
Section: Manuscript Textmentioning
confidence: 99%
“…It should be pointed out that there are many FDA approved drugs for which the mechanism is unknown. It is only in recent years that we have started to unravel the mechanism of action of such drugs that were approved decades ago (29, 30). The focus of our current efforts is on assessing pyronaridine and other clinical stage compounds as possible treatments for EBOV.…”
Section: Introductionmentioning
confidence: 99%